As leituras d'O Amanuense Belmiro: da crítica jornalística à crítica universitária - BRANDILEONE, Ana Paula Franco Nobile [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
O presente ensaio tem por objetivo percorrer algumas leituras que a crítica literária exercida nos jornais tem realizado de O amanuense Belmiro, a partir de 1937, assim como apresentar a recepção crítica desse romance de estréia de Cyro dos Anjos, no meio universitário.

The present essay has the objective to go through some readings that the literary critic exercised in the newspaper has carried out of O amanuense Belmiro from 1937 on, as well to present the critical reception of tthis premiere romance of Cyro dos Anjos in the academical environment.
The reading of O Amanuense Belmiro: from de journalistic review to the academical review The reading of O Amanuense Belmiro: from de journalistic review to the academical review
Keywords: Cyro dos Anjos; O amanuense Belmiro; literary critic; crítica literária